Vitreoretinal Injury Associated with Sports Ball Ocular Trauma - Rohowetz LJ; Fan J; Flynn HW Jr (Clinical Ophthalmology)
Landon J Rohowetz, Jason Fan, Harry W Flynn Jr Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Harry W Flynn Jr, Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, 900 NW 17th St, Miami, FL, USA, Tel +1 305 326-6148, Fax +1 305 326-6417, Email hflynn@med.miami.eduAbstract: Sports are a common cause of ocular trauma. Vitreoretinal injuries secondary to sports ball trauma can cause permanent vision loss and may be a source of significant morbidity. Trauma most frequently occurs in young males and over half of injuries involve the posterior segment. Injuries typically occur as a result of direct contact with the globe either before or after initial contact with the orbit and are dependent on the size, mass, and velocity of the ball. Compressive forces and subsequent equatorial expansion lead to direct tissue damage and dehiscence of posterior segment layers. Smaller balls with relatively high mass and velocity such as golf balls and paintballs are associated with rupture injuries while larger balls frequently cause contusive trauma and distortion of the globe which may lead to vitreoretinal traction and damage to posterior segment layers. Retinal detachment may occur and is frequently associated with retinal dialysis and giant retinal tears. Traumatic macular hole is uncommon and, unlike idiopathic macular hole, frequently closes spontaneously. The institution of eye protection standards in select sports have dramatically reduced the incidence of eye injuries. Continued evaluation of the most appropriate and logical protective measures is essential to promote the safety of all athletes and reduce the incidence of frequently-disabling ocular injury.Keywords: ocular trauma, sports injury, open globe injury, retinal detachment, traumatic macular hole